Anxiety and Depression in pre-and-post-Hematopoietic Stem Cell Transplants in SCT Center, Shariati Hospital, Tehran, Iran - Roghieh Maheri Azar; Mansoureh Nikoogoftar; Shiva Salehi; Ali Reza Zohoor (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
Introduction: In Iran along with other countries, as transplant technology progresses and advances, the number of patients undergoing transplantation is rising steadily. In order to make Stem-Cell Transplantation (SCT) safer and more effective, psychological distress of patients must be taken in to account. Patients are facing challenges pre- and post-transplantation. This study attempts to measure and compare the levels of anxiety depression before and after SCT. Method and materials:The study includes 35 patients (21 male and 14 female; mean age 34.8, range 18-60 years, 10 Hodgkin's disease, 10 MM, 9 AML and 6 ALL) who met the inclusion criteria at the time of hospitalization were selected as candidates for SCT at Shariati Hospital-Tehran, Iran. Anxiety and depression were evaluated by Hospital Anxiety and Depression Scale (HADS). Questionnaires were filled out in two steps, once within 48 hours after hospitalization and the other one on the day of discharge. Results: Level of anxiety and depression decreased from 8.64±3.42 to 6.09±2.84 and from 7.20±3.49 to 6.00±3.7, respectively (both p-values <0.001).Nobody has severe anxiety/depression pre- or post-SCT and only one patient had moderate anxiety/ depression before SCT that reduced to mild level thereafter. Conclusion: The level of anxiety and depression in transplant patients has been reduced. The findings suggest that psychological distress (anxiety, depression) should be evaluated in patients at frequent intervals. Therapeutic treatment procedure, pharmaceutical and non pharmaceutical treatment should be carried out based on the results obtained from patients under study.